CCNA routing and switching ICND2 200-105 official cert guide - Odom, Wendell; Hogg, Scott (Cisco Press, 2017)
Trust the best-selling Official Cert Guide series from Cisco Press to help you learn, prepare, and practice for exam success. They are built with the objective of providing assessment, review, and practice to help ensure you are fully prepared for your certification exam. CCNA Routing and Switching ICND2 200-105 Official Cert Guide presents you with an organized test preparation routine through the use of proven series elements and techniques. "Do I Know This Already?" quizzes open each chapter and enable you to decide how much time you need to spend on each section. Exam topic lists make referencing easy. Chapter-ending Exam Preparation Tasks help you drill on key concepts you must know thoroughly. Master Cisco CCNA ICND2 200-105 exam topics Assess your knowledge with chapter-opening quizzes Review key concepts with exam preparation tasks Practice with realistic exam questions on the CD-ROM CCNA Routing and Switching ICND2 200-105 Official Cert Guide from Cisco Press enables you to succeed on the exam the first time and is the only self-study resource approved by Cisco. Best-selling author and expert instructor Wendell Odom shares preparation hints and test-taking tips, helping you identify areas of weakness and improve both your conceptual knowledge and hands-on skills. This complete study package includes A test-preparation routine proven to help you pass the exams "Do I Know This Already?" quizzes, which enable you to decide how much time you need to spend on each section Chapter-ending and part-ending exercises, which help you drill on key concepts you must know thoroughly Troubleshooting sections, which help you master the complex scenarios you will face on the exam The powerful Pearson IT Certification Practice Test software, complete with hundreds of well-reviewed, exam-realistic questions, customization options, and detailed performance reports A free copy of the CCNA ICND2 200-105 Network Simulator Lite software, complete with meaningful lab exercises that help you hone your hands-on skills with the command-line interface for routers and switches Links to a series of hands-on config labs developed by the author Online interactive practice exercises that help you hone your knowledge More than 50 minutes of video mentoring from the author A final preparation chapter, which guides you through tools and resources to help you craft your review and test-taking strategies Study plan suggestions and templates to help you organize and optimize your study time Well regarded for its level of detail, study plans, assessment features, challenging review questions and exercises, video instruction, and hands-on labs, this official study guide helps you master the concepts and techniques that ensure your exam success. This official study guide helps you master all the topics on the CCNA ICND2 exam, including Ethernet LANs IPv4 routing protocols Wide area networks IPv4 services: ACLs and QoS IPv4 routing and troubleshooting IPv6 Network management, SDN, and cloud computing Companion DVD The DVD contains more than 300 unique practice exam questions, ICND2 Network Simulator Lite software, online practice exercises, and 55 minutes of video training. Includes Exclusive Offers for up to 70% Off Practice Tests, Video Training, and Network Simulation Software This volume is part of the Official Cert Guide series from Cisco Press. Books in this series provide officially developed exam-preparation materials that offer assessment, review, and practice to help Cisco Career Certification candidates identify weaknesses, concentrate their study efforts, and enhance their confidence as exam day nears. Also available from Cisco Press for CCNA study is the CCNA Routing and Switching ICND2 200-105 Official Cert Guide Premium Edition eBook and Practice Test. This digital-only certification preparation product combines an eBook with enhanced Pearson IT Certification Practice Test. This integrated learning package Enables you to focus on individual topic areas or take complete, timed exams Includes direct links from each question to detailed tutorials to help you understand the concepts behind the questions Provides unique sets of exam-realistic practice questions Tracks your performance and provides feedback on a module-by-module basis, laying out a complete assessment of your knowledge to help you focus your study where it is needed most Pearson IT Certification Practice Test minimum system requirements: Windows 10, Windows 8.1, Windows 7, or Vista (SP2), Microsoft .NET Framework 4.5 Client; Pentium-class 1 GHz processor (or equivalent); 512 MB RAM; 650 MB disk space plus 50 MB for each downloaded practice exam; access to the Internet to register and download exam databases.